Effects of Drop Jumps on 1000-m Performance Time and Pacing in Elite Male and Female Endurance Runners - Boullosa, Daniel; Abad, Cesar C. C.; Reis, Valter P.; Fernandes, Victor; Castilho, Claudio; Candido, Luis; Zagatto, Alessandro M. [UNESP]; Pereira, Lucas A.; Loturco, Irineu (Human Kinetics Publ Inc, 2020)
Purpose: To evaluate the effect of drop jumps (DJs) on performance time and pacing in a field test (ie, 1000 m) commonly used to evaluate endurance runners and to evaluate running and jumping performance in male and female athletes separately. Methods: Twenty elite endurance runners (male, n = 10. 27.8 [7.0] y. 62.3 [5.2] kg; female, n = 10, 25.9 [5.3] y, 51.7 [4.1] kg) competing in middle- and long-distance events participated in this study. After determination of the box height associated with the best reactive strength index, athletes randomly performed a warm-up with or without the inclusion of 5 DJs with the highest reactive strength index prior to a 1000-m track test. Performance time and pacing (250-m splits) were determined. Countermovement jump heights at different time points and blood lactate concentration after running tests were also recorded. Results: A possible faster 1000-m time (162.4 vs 165.3 s) with a very likely faster first split (38.8 vs 40.3 s) was observed in male athletes in the DJ condition. In contrast, female athletes showed a possible slower running time (186.8 vs 184.8 s) and a likely greater blood lactate concentration after the 1000-m test in the DJ condition. Male and female athletes presented greater countermovement-jump performances after warm-up and running tests in both conditions. Conclusions: The inclusion of 5 DJs with the height associated with the best reactive strength index induced a possible improvement in 1000-m performance time in elite male endurance runners. The current protocol should be avoided in female athletes.
Keywords: postactivation potentiation; plyometrics; middle-distance running; athletic performance